Proceedings of 1994 IEEE International Symposium on Electrical Insulation
DOI: 10.1109/elinsl.1994.401400
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of an oil-paper interface in presence of carbon particle contamination

Abstract: The behavior of an oilpaper interface in the presence of carbon particle contamination was investigated under AC voltage. M u e n d by an electric field perpendicular to the interface, the carbon particles are deposited on and firmly fixed to the paper surface. This constitutes an excellent means of reproducing particle contamination at the oil-paper interface, since it duplicates the particledeposition mechanism in power equipment, Field deposition of carbon contamination was found to be reproducible and easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Once mixed into the oil, the sludge acts as drifting space charge. Studies conducted on AC breakdown behavior of oil with carbon particle contamination have shown that carbon particles act as positive space charge in oil [32]. The homogenization of sludge in the oil effectively reduces the gap distance between the electrodes which reduces the charge magnitudes of streamers.…”
Section: Relevant Pd Parametersmentioning
confidence: 99%
“…Once mixed into the oil, the sludge acts as drifting space charge. Studies conducted on AC breakdown behavior of oil with carbon particle contamination have shown that carbon particles act as positive space charge in oil [32]. The homogenization of sludge in the oil effectively reduces the gap distance between the electrodes which reduces the charge magnitudes of streamers.…”
Section: Relevant Pd Parametersmentioning
confidence: 99%
“…Moreover, copper particles and air bubbles in oil trigger a higher creeping discharge of the oil-paper insulation (Thirumurugan et al, 2019). An experimental study on the effects of carbon particles on the characteristics of AC discharge of insulating paper found that carbon particles influence the development of creeping discharge of the insulating cardboard (Vincent et al, 1994). However, few studies have examined the effects of carbon particles on the properties of oil-paper insulation under a DC electric field.…”
Section: Open Accessmentioning
confidence: 99%